Strategic Alternatives for Indеpendent Fast Moving Consumer Goods Stores - Angelov, Svetoslav; Bares, Antoaneta (Research Papers, 2025)
Traditional traders of fast-moving consumer goods, also called independent traders, are facing serious difficulties in their work, mainly caused by the strong expansion of representatives of modern trade. The aim of the study is to better understand the reasons for this, as well as to clarify the opportunities they have for better performance and for redefining their commercial offer. The study uses statistical data from the National Statistics Institute, a review of literature examining the formation of various competitive advantages, practical observations and analyses of IME. Only trade in physical objects is considered, and the method is expert analysis, theoretical synthesis, graphical method and observations from commercial practice. The main conclusions are that independent traders have different alternatives for redefining their market presence by applying one or more of the indicated guidelines.
Keywords: Modern trade; Traditional trade; Independent trader; FMCG; Strategy